Effects of high temperatures on food stability: nutritional, chemical, physical, organoleptic, and microbiological impacts - Sutrisno Adi Prayitno; Dwi Retnaningtyas Utami; Rikha Indah Mahmudah (PT. Gyandharma Global Media, 2025)
Exposure to elevated temperatures during food preparation, cooking, or storage leads to various alterations that impact the quality and stability of food. This article thoroughly examines how high temperatures affect the nutritional, chemical, physical, sensory, and microbiological features of food. Although heat treatments are effective in improving food safety and prolonging shelf life, they frequently cause nutrient loss, chemical changes, modifications in texture, and shifts in sensory characteristics like flavor, smell, and visual appeal. High temperatures can trigger processes such as Maillard browning and lipid breakdown, which affect taste and can lead to the creation of potentially harmful substances. Physical changes can include protein unfolding, starch gelatinization, and moisture evaporation, all of which significantly modify the structure and texture of food. Temperature-related loss of volatile substances and flavor quality also diminishes sensory attributes. While heat processing is effective for eliminating microbes, it needs to be managed carefully to maintain food quality. The article further discusses the promise of non-thermal and hurdle technologies as viable alternatives or complements to conventional thermal methods, designed to achieve a balance between food safety and the preservation of nutritional and sensory qualities.